Moving towards universal health coverage: an assessment of unawareness of health insurance coverage status among reproductive-age women in rural northern Ghana - Edmund W Kanmiki; Ayaga A Bawah; James Akazili; John Koku Awoonor-Williams; Kassem Kassak (Elsevier, 2018)
Background: Ghana implemented a nationwide health insurance scheme in 2005 as part of efforts to ensure access to affordable and equitable health care without paying user fees at the point of service delivery. However, active enrolment has remained low even over a decade of implementing this policy. We aimed to understand some of the factors accounting for low active enrolment by examining the possibility that unawareness of insurance status could be a contributor among women from an impoverished rural setting. Methods: We used cross-sectional data from reproductive-aged women from one of Ghana's poorest and remote regions. A two-stage sampling approach was used. First, the Ghana Statistical Service purposefully sampled and provided 66 predominantly rural enumeration areas from all districts the Upper East region except Kassena-Nankana East and West Districts. Guided by this sampling frame, a household listing of members in the sampled enumeration areas was done. Second, we sampled households proportional to the population size. Within sampled households, all females between the ages of 15 and 49 years were eligible to be interviewed. In the case of the two Kassena-Nankana Districts, sampling was done using Navrongo Health Research Center demographic surveillance data, from which a random sample of 2500 women was sampled. During the survey, two questions related to the National Health Insurance Scheme (NHIS) were asked: "Have you ever registered with the NHIS?" and "Do you currently have a valid NHIS card?" If the answer to the second question was yes, the interviewer requested to see the card and confirm its validity (cards must be renewed annually). We examined the prevalence and predictors of unawareness of health insurance status using descriptive statistics, a χ2 test of association, and regression analysis. Findings: Data collection started on Oct 2, 2014, and ended on Jan 31, 2015. Of the 7693 respondents, 4900 (64%) who thought that they were actively enrolled in the NHIS could produce their insurance cards upon request. 1642 (33·5%) of these had invalid cards. Factors that significantly predicted unawareness of card invalidity were occupation, district of residence, and socioeconomic status. Farmers were the most likely to be unaware of their card validity status compared with all other occupations. Residents in five out of seven districts were less likely to be unaware of their insurance card validity. There was a consistent increase in the likelihood of unawareness with decreasing socioeconomic status. Interpretation: Unawareness of insurance card invalidity is an important contributor to low active enrolment onto Ghana's national health insurance scheme. Educational campaigns aimed at improving active health insurance membership should include messages that are tailored to populations such as farmers and low socioeconomic groups. The unawareness disparities within districts in the studied region merit further investigation. Funding: Doris Duke Charitable Foundation.